Endoplasmic Reticulum-resident Heat Shock Protein 90 (HSP90) Isoform Glucose-regulated Protein 94 (GRP94) Regulates Cell Polarity and Cancer Cell Migration by Affecting Intracellular Transport - Ghosh, Suman (J Biol Chem, 2016)
Heat shock protein 90 (HSP90) is a molecular chaperone that is up-regulated in cancer and is required for the folding of numerous signaling proteins. Consequently, HSP90 represents an ideal target for the development of new anti-cancer agents. The human HSP90 isoform, glucose-regulated protein 94 (GRP94), resides in the endoplasmic reticulum and regulates secretory pathways, integrins, and Toll-like receptors, which contribute to regulating immunity and metastasis. However, the cellular function of GRP94 remains underinvestigated. We report that GRP94 knockdown cells are defective in intracellular transport and, consequently, negatively impact the trafficking of F-actin toward the cellular cortex, integrin α2 and integrin αL toward the cell membrane and filopodia, and secretory vesicles containing the HSP90α-AHA1-survivin complex toward the leading edge. As a result, GRP94 knockdown cells form a multipolar spindle instead of bipolar morphology and consequently manifest a defect in cell migration and adhesion.